2009
DOI: 10.1016/j.bbi.2009.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Substantial reduction of naïve and regulatory T cells following traumatic stress

Abstract: Posttraumatic stress disorder (PTSD) is associated with an enhanced susceptibility to various somatic diseases. However, the exact mechanisms linking traumatic stress to subsequent physical health problems have remained unclear. This study investigated peripheral T lymphocyte differentiation subsets in 19 individuals with war and torture related PTSD compared to 27 non-PTSD controls (n=14 trauma-exposed controls; n=13 non-exposed controls). Peripheral T cell subpopulations were classified by their characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
91
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(105 citation statements)
references
References 46 publications
10
91
0
3
Order By: Relevance
“…This impact on the entire T-cell compartment is consistent with previous research in adult PTSD patients showing fewer naïve T lymphocytes but increased memory T lymphocytes [12]. Similarly, an increased ratio of memory versus naïve T cells was found in adult women with PTSD in the aftermath of childhood sexual abuse [32].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This impact on the entire T-cell compartment is consistent with previous research in adult PTSD patients showing fewer naïve T lymphocytes but increased memory T lymphocytes [12]. Similarly, an increased ratio of memory versus naïve T cells was found in adult women with PTSD in the aftermath of childhood sexual abuse [32].…”
Section: Discussionsupporting
confidence: 79%
“…the relationship between symptom severity and increased T-cell activation [8], or to associations between PTSD and decreased counts of lymphocytes, T cells [11] and naïve T lymphocytes [12]. The number of recent thymic emigrant cells (RTEs) in the T-cell compartment [13] has been found to be persistently reduced in mice showing PTSD-like behavior due to social stress [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a ∼50% drop in regulatory T cells (Tregs; CD4+CD25+FoxP3+) in PTSD patients as compared to healthy controls has also been reported [1]. This substantial decline in Tregs could bear the risk of excessive inflammation due to suboptimum control of immune responses and provide further support to the pro-inflammatory profile observed in patients with PTSD.…”
Section: Immune Imbalance: Evidence For Low-grade Inflammationmentioning
confidence: 91%
“…Lymphocytes expressing the late (CD71+) but not the early (CD25+) activation marker were also elevated in displaced women. Sommershof et al [1] found an increased percentage of both central memory (CD45RA-CCR7+) and effector memory (CD45RA-CCR7-) T cell subsets in childhood abuse-related PTSD patients. Increased percentages in CD8+ T cells expressing early activation markers (CD8+CD45RA+) in abuse-related PTSD women have also been reported [38,39].…”
Section: Immune Imbalance: Evidence For Low-grade Inflammationmentioning
confidence: 99%
See 1 more Smart Citation